Pelatihan Bisnis Plan dan Digitalisasi Marketing - Maria Silvana Mariabel Carcia; Cicilia Ayu Wulandari Nuwa; Maria Nona Dince; Dimas Relino (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Some of the indicators that can be used today include the increase in digital advertising spending, the growth of smartphone ownership that provides easy inter-net access, the improvement of telecommunications infrastructure in order to improve the quality of data access, and the launch of 4G services.